P1516DEMONSTRATION OF FLUID REMOVAL ACCURACY USING THE SC+ HAEMODIALYSIS SYSTEM. (6th June 2020) - Buckberry, Clive; Komenda, Paul; Heyes, Keith; Westenbrink, Eric; Wallace, Mark; Milad, John
Abstract: Background and Aims: Fluid management is an integral component for managing patients to correct abnormalities in plasma composition and maintain fluid balance. Consequently, accurate fluid removal during treatment is a critical design element of haemodialysis machines. The SC+ haemodialysis system developed by Quanta Dialysis Technologies, is a small, simple-to-use dialysis system designed to improve patient access to self-care and home haemodialysis. This paper describes the design, evaluation and performance of the flow balance and ultrafiltration module of SC+ to deliver specified fluid removal in accordance with the international technical standards for haemodialysis defined in IEC 60601-2-16 using a number of unique proprietary technologies. Method: SC+ uses volumetric flow balancing chambers which are contained within a single use disposable cartridge. During normal operation of SC+, dialysis fluid flows through the cartridge in discrete packets. This is achieved by the application of pneumatic pressure and vacuum to manipulate a flexible PVC membrane that, in turn, opens and closes a sequential series of valves and pump cavities that constitute the flow balance chambers. Proof of system performance was undertaken using a range of dialysers and venous pressures, with and without ultrafiltration, to quantify the net fluid removal error, in order to simulate a range of patient conditions in typical clinical practice. Results: In total, the tests comprised 22 separate runs on multiple machines, with 88 individual 30-minute measurement samples, taken over a range of environmental conditions, dialyser types (with differing KuF), dialysate flowrates, and venous pressures. Across all results, there was a mean error of 7.4g/hour rate error, (max allowed is 100g/hr) of positive flow from the blood to the dialysate side with a standard deviation of 19.88g/hr. The maximum permissible rate stated in IEC 60601-2-16 is +/-100g/hr. In specific detail, without ultrafiltration the flow balance error was measured as 2.2g/hr with a deviation of 19.0g/hr, and with ultrafiltration the mean error was 12.8g/hr with a standard deviation of 19.5g/hr. Conclusion: It has been demonstrated that flow balance error and fluid removal attainable with the SC+ haemodialysis system lies well within the acceptable standards permitted for haemodialysis machines. This essential performance parameter as defined within IEC 60601-2-16 has been demonstrated across a range of clinically relevant parameters at dialysate flow rates of up to 500ml/min